Time perception and dynamics of facial expressions of emotions. - Sophie L Fayolle (Public Library of Science (PLoS), 2014)
Two experiments were run to examine the effects of dynamic displays of facial expressions of emotions on time judgments. The participants were given a temporal bisection task with emotional facial expressions presented in a dynamic or a static display. Two emotional facial expressions and a neutral expression were tested and compared. Each of the emotional expressions had the same affective valence (unpleasant), but one was high-arousing (expressing anger) and the other low-arousing (expressing sadness). Our results showed that time judgments are highly sensitive to movements in facial expressions and the emotions expressed. Indeed, longer perceived durations were found in response to the dynamic faces and the high-arousing emotional expressions compared to the static faces and low-arousing expressions. In addition, the facial movements amplified the effect of emotions on time perception. Dynamic facial expressions are thus interesting tools for examining variations in temporal judgments in different social contexts.